Pathways to well-being : helping educators (and others) find balance in a connected world - Brooks-Young, Susan; Armstrong, Sara (International Society for Technology in Education, 2019)
This book provides an overview of each of the six elements of well-being with connections to the applicable ISTE Standards for Educators and the ISTE Standards for Education Leaders, information on the positive and negative aspects of technology related to overall well-being, reflection questions to help readers make healthy changes, and additional resources such as research, articles, books and websites.